Cybersecurity in the CAN Protocol: A Systematic Mapping of Attacks and Vulnerabilities in Practical Scenarios - Baltor, Amanda Kasat; Castelo Branco, Kalinka (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2026)
The technological evolution of vehicles has expanded their attack surface, exposing the CAN (Controller Area Network) protocol to critical vulnerabilities. This paper presents a Systematic Literature Mapping (SLM) analyzing 196 studies focused on practical experiments. Results highlight the prevalence of Spoofing and Injection attacks targeting critical functions like braking and steering. The study identifies a significant lack of standardized attack taxonomy and risk classification in the literature. Furthermore, it distinguishes between legacy architectures and emerging UN R155-compliant vehicles, which implement defenses such as Security Gateways, marking a transition towards secure-by-design automotive ecosystems.